Pravica do javnih mestnih prostorov v Sarajevu - Šamić, Dina (Urbani izziv, 2021)
Multiple socio-political and economic factors have gradually led to widespread neglect, decline, misuse, and loss of public spaces in Sarajevo. The clash between private and public interests has left physical traces in the city, recalling the importance of Lefebvre’s notion of the right to the city. In the context of the contemporary urban development of Sarajevo, this is translated into the right to shape, use, recycle, and reactivate the city’s neglected shared spaces. As implied by the title of this article, the key question addressed is to whom public space really belongs. This research proceeds from the identification of the key issues of degradation of public spaces, followed by the valorization of mainstream planning approaches and occasional bottom-up initiatives. It is argued that one of the key origins of the problem lies in dispersal and the lack of pertinent geospatial data on public spaces, as well as in the dissonance between all the relevant stakeholders. This article establishes a methodology for introducing a comprehensive, open, and interactive geospatial database as a platform for strategic planning, design, development, and maintenance of urban public spaces.
Keywords: geoprostorski podatki; geospatial databases; javni prostor; mestni prostor; podatkovne zbirke; Sarajevo; strategic planning; strateško planiranje; urban public spaces